An RBD-Fc mucosal vaccine provides variant-proof protection against SARS-CoV-2 in mice and hamsters - Yanjun Zhang; Yan Wu; Meng-Qian Zhang; Haiyue Rao; Zhaoyong Zhang; Xiangyue He; Yiwen Liang; Raoqing Guo; Yaochang Yuan; Jing Sun; Helen M. E. Duyvesteyn; Elizabeth E. Fry; et al. (npj Vaccines)
Abstract Current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines are effective against severe disease and death, but do not prevent viral infections, probably due to the limited mucosal immunity induced by intramuscular administration of the vaccine. Fusion of SARS-CoV-2 subunit immunogens with a human IgG Fc backbone can be used as a mucosal vaccine but its effectiveness in delivery in animal models, and its immunogenicity and the vaccine-induced protection against viral infections requires further studies. Here we investigate a bivalent RBD-Fc vaccine that includes the spike receptor-binding domains (RBDs) of the ancestral and BQ.1.1 variant of SARS-CoV-2. Ex vivo fluorescent imaging demonstrates that this vaccine can be effectively delivered to the lungs of mice through intranasal administration, with enhancement of retention in the nasal cavity and lung parenchyma. In mice, the vaccine elicited potent and broad-spectrum antibody responses against different variants including KP.3 which could persist for at least 3 months after booster. Importantly, it was able to induce RBD-specific mucosal IgA responses. Further, heterologous intranasal immunisation with adeno-vectored Chadv1 and RBD-Fc elicited both potent neutralising antibody and T cell responses. Immunised BALB/c and K18-hACE2-transgenic mice were also protected against viral challenge of XBB.1 and viral transmission was effectively limited in hamsters through intranasal immunisation. This work thus demonstrates the potential of RBD-Fc antigens as mucosal vaccines for prevention of breakthrough infections and onward transmission. Moreover, Fc-fusion proteins can be used as an effective mucosal vaccine strategy which can be used either alone or in combination with other vaccine technology to constitute heterologous immunisations, enabling strong protection against SARS-CoV-2 and other respiratory viruses.